GLOBOID WORM HOB - EFTIMIE Dorin; BLĂNARU Viorel (Journal of Industrial Design and Engineering Graphics, 2011)
This paper presents a new constructive solution of globoid worm hob in the globoid worm wheels gear cutting. This type of tool was created in full 3D. Technological difficulties have been overcome in the execution of this new type of hob that allow widespread use globoid worm gears.